PNPLA3 I148M polymorphism, clinical presentation, and survival in patients with hepatocellular carcinoma. - Luca Valenti (Public Library of Science (PLoS), 2013)
Background & aims Aim of this study was to evaluate whether the PNPLA3 I148M polymorphism, previously associated with hepatocellular carcinoma (HCC) risk, influences the clinical presentation of HCC and survival. Methods we considered 460 consecutive HCC patients referred to tertiary care centers in Northern Italy, 353 with follow-up data. Results Homozygosity for PNPLA3 148M at risk allele was enriched in HCC patients with alcoholic liver disease or nonalcoholic fatty liver disease (ALD&NAFLD: relative risk 5.9, 95% c.i. 3.5-9.9; other liver diseases: relative risk 1.9, 95% c.i. 1.1-3.4). In ALD&NAFLD patients, the PNPLA3 148M allele was associated with younger age, shorter history of cirrhosis, less advanced (Child A) cirrhosis at HCC diagnosis, and lower HCC differentiation grade (p<0.05). Homozygosity for PNPLA3 148M was associated with reduced survival in the overall series (p = 0.009), and with a higher number of HCC lesions at presentation (p = 0.007) and reduced survival in ALD&NAFLD patients (p = 0.003; median survival 30, 95% c.i. 20-39 vs. 45, 95% c.i. 38-52 months), but not in those with HCC related to other etiologies (p = 0.86; 48, 95% c.i. 32-64 vs. 55, 95% c.i. 43-67 months). At multivariate Cox regression analysis, homozygosity for PNPLA3 148M was the only negative predictor of survival in ALD&NAFLD patients (HR of death 1.57, 95% c.i. 1.12-2.78). Conclusions PNPLA3 148M is over-represented in ALD&NAFLD HCC patients, and is associated with occurrence at a less advanced stage of liver disease in ALD&NAFLD. In ALD&NAFLD, PNPLA3 148M is associated with more diffuse HCC at presentation, and with reduced survival.